An Analysis of Content Feasibility from BSNP on “Bahasa Inggris” Textbook for the XI Grade - Apta Vania Putri Triyanto; Lidiyatul Izzah (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2022)
Based on the 2013 curriculum, this study analyzes an English textbook for senior high school students in the XI grade entitled